Polyethyleneimine-collagen composite scaffold and preparation and application thereof
Patent Information
- Application Number
- CN202610619463.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-08
- Publication Date
- 2026-10-27
AI Technical Summary
然而,目前对聚阳离子,特别是具有高电荷密度和丰富功能基团的聚乙烯亚胺(PEI)在胶原矿化中的应用探索仍很有限
本申请的复合支架成功将引导矿化、抗菌、抗酶解和主动促成骨四大关键功能整合于一体。不同于传统仅聚焦于矿化的材料,该支架通过聚乙烯亚胺(PEI)的引入,同时赋予了材料接触抑制细菌(如金黄色葡萄球菌、变异链球菌)的能力、抵抗胶原酶水解的稳定性,以及促进骨髓间充质干细胞成骨分化的生物活性。这种“四位一体”的特性使其特别适用于复杂微环境(如感染性骨缺损)下的修复与再生;
Smart Images

Figure CN122973707A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of biomaterials technology, and in particular to a polyethyleneimine-collagen composite scaffold and its preparation and application. Background Technology
[0002] Mineralized collagen (MC) is the basic structural unit of natural hard tissues (such as bone and dentin). It endows tissues with excellent mechanical properties and biological functions by orderly arranging amorphous calcium phosphate (CaP) minerals within a collagen template to form a complex multi-level structure. Mimicking this natural process to construct biomimetic mineralized collagen scaffolds is a core research area in the field of bone tissue regeneration engineering.
[0003] Traditional biomimetic mineralization strategies primarily rely on negatively charged polyanions (such as polyacrylic acid (PAA) and polyaspartic acid (PAsp)) to stabilize amorphous calcium phosphate (ACP) precursors. Through the polymer-induced liquid precursor (PILP) mechanism, minerals are guided to penetrate specific interstitial regions of collagen fibers, achieving intrafiber mineralization. However, this polyanion-dominated system has limitations. First, it focuses mainly on achieving the mineralization process, while insufficiently considering the complexity of the bone defect microenvironment in clinical applications (such as susceptibility to bacterial infection and the presence of various hydrolytic enzymes), resulting in materials that often lack sufficient antibacterial and anti-enzymatic properties. Second, its regulatory mechanism is mainly based on electrostatic attraction, leading to a relatively simplistic theoretical model.
[0004] In recent years, studies have found that positively charged polycations (such as polyallylamine hydrochloride (PAH)) can also effectively guide collagen mineralization, and their mechanism of action may involve factors such as osmotic pressure. This has broadened our understanding of the selection of mineralization regulators and mineralization theory. However, current research on the application of polycations, especially polyethyleneimine (PEI) with high charge density and abundant functional groups, in collagen mineralization remains limited. As a cationic polymer, PEI has been widely used as a gene carrier and antibacterial agent due to its strong cationic properties and ability to interact with biomolecules, but its potential in constructing multifunctional mineralized collagen scaffolds has not yet been fully explored. Summary of the Invention
[0005] In order to overcome the above-mentioned shortcomings of the prior art, the purpose of this invention is to provide a polyethyleneimine-collagen composite scaffold and its preparation and application.
[0006] The technical solution adopted by this invention to solve its technical problem is: a method for preparing a polyethyleneimine-collagen composite scaffold, comprising the following steps: S1: Construction of PEI-collagen scaffold; S2: Mineralization of PEI-collagen.
[0007] As a further improvement of the present invention, step S1 includes the following steps: The collagen material is immersed in the polyethyleneimine solution to carry out a cross-linking reaction, thereby obtaining a polyethyleneimine-collagen composite scaffold precursor.
[0008] As a further improvement of the present invention: the concentration of the polyethyleneimine solution is 0.5 mM to 5 mM; the polyethyleneimine solution contains a crosslinking agent, the crosslinking agent comprising 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide.
[0009] As a further improvement of the present invention: the crosslinking reaction is carried out in a buffer solution with a pH of 5.0-6.0, at a reaction temperature of 15-30°C, and for a reaction time of 12-48 hours.
[0010] As a further improvement of the present invention, step S1 includes the following steps: PEI was dissolved in 0.1 M morpholine ethanesulfonic acid containing 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide for esterification, and then incubated with a collagen membrane at room temperature.
[0011] As a further improvement of the present invention, step S1 further includes the following step: The membrane sample was rinsed with distilled water to obtain the PEI-collagen model.
[0012] As a further improvement of the present invention, step S2 includes the following steps: The composite scaffold is immersed in a mineralization solution containing calcium and phosphate ions and mineralized at 30-40°C for 5-20 days to obtain a mineralized polyethyleneimine-collagen composite scaffold.
[0013] The present invention also includes a polyethyleneimine-collagen composite scaffold, which is prepared by the method described above for preparing a polyethyleneimine-collagen composite scaffold.
[0014] The present invention also includes the application of a polyethyleneimine-collagen composite scaffold, wherein the polyethyleneimine-collagen composite scaffold prepared by the method described above is used in bone defect repair, bone tissue regeneration or bone infection control.
[0015] As a further improvement of the present invention: the polyethyleneimine-collagen composite scaffold is used as a bone filler, bone tissue engineering scaffold, or coating.
[0016] Compared with the prior art, the beneficial effects of the present invention are: This application's composite scaffold successfully integrates four key functions: guided mineralization, antibacterial activity, anti-enzymatic activity, and active osteogenic stimulation. Unlike traditional materials that focus solely on mineralization, this scaffold, through the introduction of polyethyleneimine (PEI), simultaneously endows the material with the ability to inhibit bacteria (such as Staphylococcus aureus and Streptococcus mutans), resist collagenase hydrolysis, and promote osteogenic differentiation of bone marrow mesenchymal stem cells. This "four-in-one" characteristic makes it particularly suitable for repair and regeneration in complex microenvironments (such as infected bone defects). Breaking away from traditional mineralization strategies that primarily rely on polyanions (such as PAA), this study innovatively employs the cationic polymer PEI as a modifier. Molecular dynamics simulations (MDS) confirm that the PEI-collagen system exhibits a unique electrostatic adsorption preference for phosphate ions (PO4³⁻) and can promote the migration of mineralization precursors by generating osmotic pressure, providing a novel and effective mineralization driving force. The prepared scaffold can guide the orderly deposition of hydroxyapatite (HAP) crystals inside and between collagen fibers, forming a "brick-and-mortar" multi-level structure similar to natural bone, thereby better mimicking the mechanical and biological microenvironment of natural bone. Attached Figure Description
[0017] To illustrate the technical solution more clearly, the accompanying drawings used in the implementation will be briefly introduced below.
[0018] Figure 1 This is a schematic diagram illustrating the use of BMSC adhesion and proliferation in this invention.
[0019] Figure 2 Synthesis and characterization of PC fibers for this invention (n = 3); (A) ATR-FTIR spectrum, (B) Surface potential distribution map, (C) Water contact angle measurement, (D) Surface Zeta potential assessment, (E) TNBS test showing amino group changes, (F) Young's modulus, (G) Anti-enzymatic hydrolysis assessment of BC, PC2k, and PC25k, (H) High-performance liquid chromatography results of BC, PC2k, and PC25k in guanidine hydrochloride and collagenase-treated media. **p<0.01, ***p<0.001, ****p<0.0001.
[0020] Figure 3 TEM characterization of PC fiber mineralization according to the present invention (n = 3); (AC) Mineralization of PC2k in CaP solution: (A) Low-magnification image of heavily mineralized collagen lobules, showing mineralized nodules within and between fibers; (B) High-magnification image showing fully mineralized collagen lobules (irregular circles) and interfibrillary crystals (hollow arrows); (C) SAED image of mineralized PC2k; (DF) Mineralization of PC25k in CaP solution: (D) Low-magnification and (E) high-magnification images showing intrafibrillary mineralization (white crosshairs) and extrafibrillary mineral deposits (finger-like); (F) SAED image of mineralized PC25k; (GI) Mineralization of BC in PAA-CaP solution: (G) Mineralized collagen lobules after 14 days showing heavily intrafibrillary mineralization, but no obvious signs of interfibrillary mineralization (arrows); (H) Intrafibrillary mineralization within longitudinally sliced collagen fibers; (I) SAED image of PAA-CaP treated collagen; (JL) BC mineralization in CaP solution: (J) Low-magnification and (K) high-magnification images of BC show typical collagen fiber morphology with no obvious mineralization points, (L) SAED image of mineralized BC.
[0021] Figure 4 This is a STEM-EDX elemental distribution diagram (n = 3) of the mineralized PC fiber of this invention; (AD) STEM-EDX analysis of mineralized PC2k fibers: (A) Low-magnification and (B) high-magnification images showing intrafiber crystals highly oriented along the collagen axis and cloud-like interfiber crystals; (C) Elemental distribution map of PC2k lobules; (D) Elemental distribution maps representing N, Ca, P, and O, respectively; (EH) STEM-EDX analysis of mineralized PC25k fibers: (E) Low-magnification and (F) high-magnification images showing extensive intrafiber and interfiber crystals; (G) Elemental distribution map of PC25k lobules; (H) Elemental distribution maps representing N, Ca, P, and O, respectively.
[0022] Figure 5 AFM and dynamic ATR-FTIR characterization of the mineralized PC fibers of this invention (n = 3); (A) Representative AFM images of collagen fibers mineralized in CaP solution. (B) Changes in collagen fiber diameter after mineralization. (C) Dynamic ATR-FTIR spectra of PC2k and PC25k during mineralization. **p<0.01, ***p<0.001, ****p<0.0001.
[0023] Figure 6 Molecular dynamics simulations (MDS) of BC and PC2k mineralization for this invention (n = 3); (A) Schematic diagram of BC and PC2k collagen structures. (B) Containing mineralized precursors (simplified as Ca ions and PO4). 3- (C) Schematic diagram of collagen structure; simulation time: 100 ns; (D) Changes in root mean square deviation (RMSD) of collagen molecules; (E) Changes in radius of gyration (Rg); (F) Changes in hydrogen bond distribution between phosphate ions and collagen fibers; (G) Radial distribution function (RDF) of Ca²⁺ among BC, PC₂k, and PEI. 3- Radial distribution function (RDF) between BC, PC2k, and PEI; (H)Ca²⁺ with BC, and PO₄ 3- Changes in binding energy between Ca²⁺ and PC, and PO₄²⁻. 3- Changes in binding energy between PC2k and PC2k.
[0024] Figure 7 Characterization of the antibacterial effect of the PC fiber of the present invention.
[0025] (A) (Left) Live / dead staining of Staphylococcus aureus and (right) Streptococcus mutans on the surface of BC, PC2k and PC25k fibers; (B) Representative SEM images of Staphylococcus aureus and (right) Streptococcus mutans on the surface of BC, PC2k and PC25k fibers.
[0026] Figure 8 The in vitro cell compatibility and bioactivity of the PC fibers of this invention (n = 3); (A) CCK-8 results of BMSCs cultured on mineralized PC fibers; (B) SEM image of BMSCs cultured on mineralized PC fibers; (C) CLSM image of BMSCs cultured on mineralized PC fibers; (D) Expression levels of osteogenic-related genes in BMSCs cultured on mineralized fibers, including Alp, Col1, Opn, Runx2, and Vegf. *p<0.05, **p<0.01.
[0027] Figure 9 This is an electron micrograph of the polyethyleneimine-collagen composite scaffold of the present invention.
[0028] Figure 10 The images show a macroscopic image (left 1) and a scanning electron microscope microstructure (left 2) of the porous mineralized collagen tooth extraction socket filling plug of the present invention; the dense layer (left 3) and the mineralized layer (left 4) of the bilayer mineralized collagen induction membrane. Detailed Implementation
[0029] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below in conjunction with specific embodiments and corresponding drawings. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0030] It should be noted that the terms "first," "second," etc., in the specification, claims, and accompanying drawings of this invention are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence. It should be understood that such data can be interchanged where appropriate so that the embodiments of the invention described herein can be implemented in orders other than those illustrated or described herein. Furthermore, the terms "comprising" and "having," and any variations thereof, are intended to cover a non-exclusive inclusion; for example, a process, method, system, product, or apparatus that comprises a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to such processes, methods, products, or apparatus.
[0031] The microenvironment of bone defects, especially infectious or large-area defects, is extremely complex: there is a risk of bacterial infection, the activity of various hydrolytic enzymes (such as collagenase), and the need for efficient guidance of bone regeneration. However, traditional and most existing biomimetic mineralization material designs primarily focus on achieving mineralization as a single or primary goal. These materials lack the ability to resist bacterial adhesion and proliferation, easily becoming a breeding ground for biofilms in infected environments, leading to implantation failure. Their weak resistance to in vivo enzymatic hydrolysis (especially collagenase) may cause premature degradation before fulfilling their purpose, affecting the long-term stability of repair. Their osteogenic effect mainly relies on passive osteoconductivity (providing a scaffold), with limited ability to actively induce osteogenic differentiation of stem cells. To achieve mineralization, traditional techniques heavily rely on negatively charged polyanions (such as polyacrylic acid PAA) as regulators, attracting calcium ions electrostatically to form a liquid precursor (PILP) to guide mineralization. Research has long focused on polyanions, with insufficient exploration of other types of regulators such as polycations, limiting the diversity of material design and the development of new functions. Polyanions themselves typically lack strong antibacterial properties or significant cell signaling activation capabilities, making it difficult to endow materials with the aforementioned comprehensive functions through a single component. Although the PILP mechanism is widely accepted, mineralization is a complex process driven by multiple factors. Existing research mainly emphasizes electrostatic interactions, with insufficient attention paid to other key driving forces and their synergistic effects, such as osmotic pressure, steric hindrance, and polymer topology (e.g., the difference between branched and linear polymers). Furthermore, the lack of a clear molecular-level explanation of how polycations promote mineralization hinders their rational design and application.
[0032] To address the above problems, this invention provides a polyethyleneimine-collagen composite scaffold, its preparation and application, comprising the following steps: 1. Construction and characterization of PEI-collagen scaffolds: Esterification was performed using 1.25 mM PEI (2 kDa or 25 kDa) dissolved in 0.1 M 2-morpholine ethanesulfonic acid (MES buffer, pH 5.5) containing 40 mM 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide (EDC) and 100 mM N-hydroxysuccinimide (NHS). After 30 minutes, the collagen membrane was added to the solution and incubated at room temperature for 24 hours. The membrane was then rinsed three times with distilled water for 15 minutes each time, serving as a PEI-collagen (2 kDa or 25 kDa) model. For the naked collagen control group, the collagen membrane was treated with only EDC / NHS without the addition of PEI.
[0033] The samples were characterized using a series of analytical techniques, including Fourier transform infrared spectroscopy (FTIR; Vertex 70, Bruker, Germany), in the range of 400–4000 cm⁻¹. -1 Surface zeta potential (SurPASS 3, Anton Paar, Austria) at 25°C; high performance liquid chromatography (HPLC) using 4 M guanidine hydrochloride solution or 0.1 mg / mL collagenase solution; atomic force microscopy (AFM; Dimension Icon, Bruker, Germany) and 2,4,6-trinitrobenzenesulfonic acid (TNBS) assay to evaluate the crosslinking of PEI with collagen fibers.
[0034] 2. Mineralization of PEI-collagen: Equal volumes of 9 mM CaCl2·2H2O and 4.2 mM K2HPO4 solutions were mixed to obtain a CaP mineralization solution. Both solutions were prepared using 10 mM Hepes buffer containing 15 mM NaCl, with a final pH of 7.4. Collagen membranes were incubated in the CaP mineralization solution at 37°C for 14 days. For the positive control group, 40 kDa PAA was added to the mineralization medium until a concentration of 50 μg / mL was reached. The mineralization solution was changed every 2 days. After mineralization, the collagen membranes were washed three times with deionized water and then lyophilized for subsequent experiments.
[0035] 3. Characterization of mineralized PEI-collagen: 3.1. Transmission Electron Microscopy (TEM) The mineralized collagen membrane was first fixed overnight in 2% glutaraldehyde, and then dehydrated using a series of ethanol solutions with concentrations increasing from 50% to 100%. The sample was then immersed in propylene oxide and embedded in epoxy resin. Ultrathin sections were obtained and observed by TEM (JEM-1400plus JEOL, Japan) at 200 kV. The crystal structure of the infiltrated minerals was identified by selected area electron diffraction (SAED).
[0036] 3.2. Scanning Transmission Electron Microscopy (STEM) STEM images of ultrathin sections of mineralized collagen membranes loaded on a TEM grid were acquired directly on a Talos FEI F200X (Thermo Fisher Scientific, USA) at an accelerating voltage of 200 kV without uranium oxide zinc staining.
[0037] 3.3. Dynamic ATR-FTIR During the mineralization process, the infrared spectrum of the PEI-collagen membrane was monitored every 24 hours for 7 days. The mineralized PEI-collagen membrane was thoroughly rinsed with deionized water and dried using a vacuum dryer. Data were collected from 4000 to 400 cm⁻¹ using a Vertex 70 FT-IR spectrometer (Bruker, USA). -1 The spectrum within the range. The spectral intensity is plotted as a 3D image using MATLAB software.
[0038] 3.4. Atomic Force Microscopy (AFM) Reconstituted type I collagen fibers were coated onto 25 × 25 mm mica discs. The control group consisted of mica discs coated with bare collagen fibers mineralized in PAA-CaP solution. The morphology of the mineralized collagen was observed using a Dimension Icon (Bruker, USA).
[0039] 4. Molecular Dynamics Simulation (MDS) MD simulations were performed using GROMACS 2019.6, employing an Amber14SB all-atom force field and a transferable intermolecular potential 3P (TIP3P) water model. The simulations were run for 100 ns to investigate the adsorption behavior of calcium and phosphate ions on the collagen model. During the MD simulations, all involved hydrogen bonds were constrained using a Linear Constraint Solver (LINCS) algorithm with an integration step size of 2 fs.
[0040] 5. Antibacterial test and enzyme activity measurement 5.1 Antibacterial test The antibacterial activity of PEI-collagen against Staphylococcus aureus and Streptococcus mutans was tested. Staphylococcus aureus and Streptococcus mutans were inoculated into broth medium and incubated in a bacterial incubator at 37°C. 100 μL of bacterial suspension (10... 9 Cells / mL were inoculated together with PEI-collagen membranes placed in 96-well plates. Naked collagen membranes inoculated with bacteria served as a control. After 24 hours of incubation, bacterial viability assay reagent (SYTO 9, PI) was added to the samples. Images were captured using a FLUOVIEW FV3000 (Olympus Corporation, Japan). The morphology of different bacterial samples after critical point drying was then observed using SEM.
[0041] 5.2 Enzyme Activity Measurement Lyophilized cross-linked collagen (5 mg) was incubated at 37°C for 1 hour in 0.1 M Tris-HCl (pH 7.4) containing 0.05 M CaCl2. Then, 300 μL of 0.1 wt% collagenase was added to 1 mL of 0.1 M Tris-HCl (pH 7.4). The dissolved solution was centrifuged, and the supernatant was used to analyze the hydroxyproline (Hyp) content. The absorbance of each sample was read at 550 nm using a spectrophotometer.
[0042] 6. Osteogenesis Test 6.1. Cell Culture and Inoculation Rat bone marrow mesenchymal stem cells (BMSCs) were purchased from Guangzhou Jiening Biotechnology Co., Ltd. BMSCs were cultured in modified α-minimum essential medium (α-MEM) supplemented with 10% fetal bovine serum at 37°C in a humidified incubator with 5% CO2. Third-generation cells were used in subsequent experiments. Subsequently, BMSCs were isolated from the culture dishes using trypsin solution and cultured at 1×10⁻⁶ cells / mL. 5 Cells were seeded at a concentration of [number] cells / mL onto collagen membranes in 24-well plates. Cells cultured on bare collagen fibers were used as a control, and the viability of BMSCs on different membranes was assessed using the CCK-8 assay.
[0043] 6.2. qRT-PCR analysis of OPN immunofluorescence and osteogenic-related gene expression Immunofluorescence staining was used to assess the expression of the osteogenic marker OPN in BMSCs, and cell imaging was performed using a FLUOVIEW FV3000 (Olympus Corporation, Japan). After 14 days of incubation of collagen samples, the mRNA expression levels of ALP, COL1, OPN, RUNX2, and VEGF were assessed using qRT-PCR (Table 1). GAPDH was used as an internal control gene. This experiment was performed using the SYBRPremix Ex Taq II (Takara) kit on an Applied Biosystems 7300 real-time quantitative PCR system (Thermo Fisher Scientific, USA) according to previously studied methods.
[0044] GADPH ATC CTG TAG GCC AGG TGA TG AGG CTC AAG GGC TTT TAA GG ALP CTC TGG ACT TGG TGG TCA CA ACG TTC CGA TCC TGA GTG G COL1 CCT GAC GCA TGG CCA AGA AGA CA CGG GCA GAA AGC ACA GCA CTC OPN TGG CTG AAT TCT GAG GGA CTA AC TTC TGA GAT GGG TCA GGC AC RUNX2 GGG AAC CAA GAA GGC ACA GA ACT TGG TGC AGA GTT CAG GG VEGF GTC CCA TGA AGT GAT CAA GTT C TCT GCA TGG TGA TGT TGC TCT CTG Table 1 Primer sequences used for qRT-PCR 7. Statistical Analysis In the statistical analysis, the normality and homogeneity of variance of the obtained dataset were first verified. Under the premise that the above assumptions were met, parametric statistical methods were used for analysis. One-way ANOVA was used for comparisons between groups, and Dunnett's post-hoc test was used for multiple comparisons. All statistical analyses were performed using GraphPad Prism 9 software. Statistical significance was defined as: **p < 0.05, **p < 0.01, ***p < 0.001, and ****p < 0.0001. This application characterizes and verifies the performance of the composite scaffold prepared according to the present invention using the following methods: (1) Characterization of polyethyleneimine-collagen composite scaffold High-performance liquid chromatography (HPLC) was used to analyze collagen samples treated with guanidine hydrochloride solution, such as... Figure 2 The results show a characteristic peak at 3.12 min, indicating disruption of the left-handed α-chain structure and the triple helix of type I collagen. In the 2 kDa and 25 kDa molecular weight groups, a weak peak was detected at approximately 1.87 min, corresponding to a small amount of free protonated branched polyethyleneimine, suggesting the formation of stable covalent bonds between branched polyethyleneimine and collagen. Further analysis using collagenase treatment showed that the peak intensity of free protonated branched polyethyleneimine at 1.98 min and 1.87 min was higher in the 25 kDa group than in the 4 kDa group, indicating a slightly higher number of non-specific amino acid cleavage sites in the structure of larger molecular weight branched polyethyleneimine.
[0045] Surface zeta potential measurements showed that the zeta potentials of the branched polyethyleneimine-collagen composite scaffolds were 18.25 ± 0.55 mV and 17.60 ± 0.12 mV, respectively, while the bare collagen membrane was negatively charged. Fourier transform infrared spectroscopy analysis showed that the 2 kDa and 25 kDa branched polyethyleneimine-collagen composite scaffolds exhibited activity in the amide I band (1650 cm⁻¹). -1 ), Amide II band (1554 cm) -1 ) and amide III band (1240 cm) -1 The absorption peak intensity at () is higher than that of the bare collagen membrane, indicating an increase in amide bond content. These results collectively confirm that a stable covalent bond has formed between branched polyethyleneimine and collagen fibers.
[0046] The water contact angle measurement results showed that the average contact angles of the 2 kDa and 25 kDa branched polyethyleneimine-collagen composite scaffolds were 34.78° and 41.38°, respectively, while the average contact angle of the bare collagen membrane was 29.83°. This indicates that the hydrophobicity of the composite scaffold was enhanced after modification with branched polyethyleneimine, and this change is consistent with its covalent cross-linked structure.
[0047] (2) Anti-enzymatic properties TNBS and type I collagenase assays showed a significant increase in the -NH2 functional groups and a decrease in the free hydroxyproline content in the PEI-collagen group, further confirming the cross-linking effect of PEI. Figure 3 As shown, this indicates enhanced resistance to enzymatic degradation. Furthermore, AFM analysis revealed that the Young's moduli of the 2 kDa and 25 kDa PEI-collagen groups were 2.16 GPa and 2.84 GPa, respectively, significantly higher than the 0.32 GPa of the blank collagen, indicating enhanced resistance to deformation. Simultaneously, PEI crosslinking led to an increase in surface contact angle and a decrease in hydrophilicity.
[0048] (3) Mineralization activity detection The branched polyethyleneimine-collagen composite scaffold was mineralized in a mineralization solution containing calcium and phosphate ions. For example... Figure 4As shown, after mineralization treatment, the 2 kDa branched polyethyleneimine-collagen composite scaffold exhibits distinct and uniform intrafiber mineralized collagen sheets, with crystals arranged parallel to the long axis of the collagen fibers. The original banded structure of the collagen disappears due to the high degree of mineralization. Simultaneously, interfiber mineralization was also observed in this group, with dispersed large crystals of approximately 200 nm in size. Selected area electron diffraction (SED) patterns show that the diffraction rings of the mineral phase correspond to the crystal plane features of hydroxyapatite, indicating that the mineral phase is hydroxyapatite. Similar results were observed in the 25 kDa branched polyethyleneimine-collagen composite scaffold. Cross-sectional images show intrafiber mineralization, with mineral crystals dispersed on the fiber exterior. Hydroxyapatite crystals are deposited not only in the intercellular spaces of the collagen but also extend into the extended regions, indicating that both intrafiber and interfiber mineralization exist simultaneously in the branched polyethyleneimine-collagen composite scaffold.
[0049] As a control, the blank collagen scaffold mineralized in polyacrylic acid-calcium phosphate solution showed relatively uniform mineralization characteristics, with higher mineralization in the peripheral regions, but no coarse cord-like minerals were observed; although ordered interfibrillary mineralization was visible, its selected area electron diffraction pattern also confirmed that the mineral phase was hydroxyapatite. However, transmission electron microscopy observation showed that the mineral deposition of the branched polyethyleneimine-collagen composite scaffold group was more ordered than that of the polyacrylic acid-calcium phosphate group.
[0050] Further analysis of the elemental distribution after mineralization was conducted using scanning transmission electron microscopy. For example... Figure 5 As shown, significant intrafiber and interfiber mineralization was observed in both the 2kDa and 25kDa branched polyethyleneimine-collagen composite scaffolds. Large, orderly arranged plate-like crystals, with lengths reaching hundreds of nanometers, were observed in both groups of samples. Elemental mapping analysis revealed that calcium (Ca), phosphorus (P), and oxygen (O) were uniformly distributed within the fibers.
[0051] Three-dimensional observation of the collagen membrane showed that mineralization contours within and between the strip-like fibers could be clearly detected, and their morphological characteristics were similar to those of natural woven bone. Figure 4 The classic negatively charged polyacrylic acid system, on the other hand, exhibits a uniform, fibrous mineralization morphology. Figure 4 Studies have shown that different non-collagen regulatory proteins can induce the formation of mineralized structures with varying morphologies in bone tissue; polyethyleneimine hydrogels can induce the formation of spherical hydroxyapatite particles, polyvinylphosphonic acid / polyacrylic acid systems can induce the formation of needle-like crystals, while the addition of alkaline earth metals can induce the formation of rod-like polycrystalline structures. Therefore, the difference in mineralization morphology between polyacrylic acid and branched polyethyleneimine-collagen composite scaffold systems in this study can be attributed to the different molecular arrangements of linear polyacrylic acid and branched polyethyleneimine.
[0052] Studies have shown that the formation of mineralized collagen is influenced by multiple factors, including capillary action, size exclusion effect, electrostatic attraction, interfacial energy, and Gibbs-Donnan equilibrium. Based on the polymer-induced liquid precursor (PILP) theory, Grower emphasized the importance of liquid-liquid separated precursor phases in biomineralization systems. Recent research suggests that not only amorphous PILP precursors, but also smaller stable (metastable) prenuclear clusters (PNCs, approximately 0.87 nm in diameter) can induce the formation of mineralized collagen. The successful formation of mineralized collagen may not depend on a single factor or structure, but rather on the combined effect of multiple factors. In the absence of additional precursor inhibitors, SEM morphology and AFM diameter measurements showed that the degree of ordered mineralization of PEI-collagen was higher than that of the blank collagen / PAA-ACP system (Figures 4 and 5). Besides PAH and dopamine, which have been reported previously, PEI in this system represents another effective collagen surface modification strategy.
[0053] AFM and Dynamic FTIR Assessment: AFM images and statistical data showed a significant increase in collagen diameter within the PEI-collagen group (Figure 6). Mineralization of the PEI-collagen membrane over 7 days was monitored by dynamic FTIR (Figure 6), revealing an OPO stretching vibration absorption peak at 1078 cm⁻¹, with the peak height gradually increasing over time, indicating the deposition of calcium phosphate minerals. However, a peak at 1650 cm⁻¹ was observed. -1 The peak height of the amide bond decreased significantly on days 2-3, and then remained stable, suggesting that mineral crystals gradually deposited on the amide bonds of collagen fibrils. Figure 6 The increase in Young's modulus ( Figure 3 Enhanced anti-enzymatic properties Figure 3 ), mineralization capacity in artificial mineralizing solutions ( Figure 4 , 5 6) and the increase in fiber bandwidth in AFM images ( Figure 6 All studies confirmed the alteration of the physical properties of PEI-collagen. Similarly, Zhang et al.'s research showed that PEI crosslinking can enhance the tensile strength and surface hardness of cellulose acetate (CA) membranes. This phenomenon may be due to the additional crosslinking between PEI and type I collagen reducing the slippage of α chains between collagen molecules and covering the enzyme cleavage sites.
[0054] (4) Molecular dynamics simulation To further elucidate the molecular migration mechanism of the PEI-collagen system, molecular dynamics simulations were performed. The blank collagen and 2 kDa PEI-collagen mineralization systems were essentially stable after 60 ns (Figures 6A and 6B), with root mean square deviations (RMSD) of 4.654 ± 0.146 nm and 3.804 ± 0.161 nm, respectively, representing the total atomic deviation (Figure 6C). The higher RMSD value of the PEI-collagen model indicates greater structural fluctuations in collagen fibers. Niu et al. also proposed this swelling phenomenon caused by osmotic pressure in their study of PAH-collagen. Both the PEI-collagen and blank collagen systems exhibited relatively stable states, with average radii of gyration (Rg) characterizing the overall structural changes of 16.534 ± 0.004 nm and 16.533 ± 0.005 nm, respectively (Figure 6D). Although PEI crosslinking leads to structural fluctuations in PEI-collagen, it has no significant impact on the stability of the rest of the system.
[0055] To analyze phosphate ions (PO4) 3- The interaction between PO4 and the collagen model was investigated, and the number of hydrogen bonds was calculated. The results showed that the number of hydrogen bonds in the blank collagen model was 10.99±3.44 after 60 ns, while that in the PEI-collagen group was 25.19±3.94, indicating that PO4 in the PEI-collagen group... 3 - The interaction between them is stronger (Figure 6E). Subsequently, the interaction between calcium ions (Ca) during molecular dynamics simulations was analyzed. 2 + ) and PO4 3 - The radial distribution function (RDF) of collagen and polymer PEI was compared with that of collagen. The results showed peaks at approximately 0.2 nm and 0.25–0.30 nm, corresponding to PO4, respectively. 3 - (Hydrogen bonds) and Ca 2 + The combination of (Ca) 2 + (Figure 6F, G). PEI-collagen showed a higher peak at 0.2 nm than blank collagen (Figure 6F), while blank collagen showed a stronger peak in the 0.25–0.3 nm range (Figure 6G). These results indicate that PEI-collagen exhibits better adsorption for PO43-, while blank collagen shows better adsorption for Ca. 2 + The adsorption of + is better.
[0056] To evaluate Ca 2 + and PO4 3 - The binding forces of the ions were investigated, and the changes in their binding energies with the collagen model were calculated (Figure 6H, I). The results show that in the blank collagen model, Ca... 2+The binding energy (-3551.26±380.13 kJ / mol) is stronger than that of PO4. 3 - Ions (-756.76±298.22 kJ / mol). In the PEI-collagen model, PO4... 3 - The binding energy of the ions (-3780.70±380.82 kJ / mol) is higher than that of Ca in the blank collagen model. 2+ Ions (-1849.58±286.47 kJ / mol) (Figure 6I). Overall, the PEI-collagen model for Ca 2+ and PO4 3 - Ions are more strongly adsorbed. Previous studies have shown that high concentrations of Ca... 2+ and PO4 3 - Ions can accelerate intrafiber mineralization, and most modifiers are designed to capture Ca. 2+ The results of this study indicate that it primarily enhanced the response to PO4. 3 - Adsorption. Furthermore, the contraction and ion adsorption of PEI-collagen in molecular dynamics simulations may indicate the combined effect of osmotic pressure and electrostatic adsorption forces.
[0057] In the absence of additional precursor stabilizers, SEM morphology and AFM diameter measurements showed that the PEI-collagen surface-modified system exhibited a higher degree of mineralization than the blank collagen / PAA-ACP system (Figures 3 and 4). In molecular dynamics simulations, PEI molecules bind to the collagen surface, forming the collagen's tertiary structure and chelating a large amount of PO4. 3 - Ions. This internal trapping of PO4 3 - The structure of the ions resembles a "salt bridge," which is the aggregation of charged residues between secondary collagen chains. These are generally considered to be calcium and phosphate reserve nodules that trigger the formation of mineralized collagen. In summary, in the absence of liquid nucleation inhibitors, the aggregation of PEI molecules between collagen chains may increase osmotic pressure, store calcium and phosphate ions, and provide binding sites for heterogeneous nucleation.
[0058] (5) Antibacterial activity test Bacterial infection is a key risk factor in hard tissue regeneration. The main antibacterial mechanism of polycations is the bacterial membrane-lytic activity generated by their dense, positively charged surface, a mechanism independent of specific protein targets. Because Gram-positive bacteria possess thick monolayer membranes and develop resistance slowly, this study selected two representative Gram-positive bacteria (Staphylococcus aureus and Streptococcus mutans) as antibacterial targets. In bone infections, Staphylococcus aureus is the primary and most destructive pathogen due to its ability to cause long-term infection within osteoblasts. Streptococcus mutans, on the other hand, is a core bacterium in dental tissue, a major colonizer of dental plaque, and one of the most important acid-producing bacteria leading to dental caries.
[0059] The antibacterial activity of the mineralized composite scaffold was evaluated using a live / dead bacteria staining method. The results showed a significant decrease in bacterial density on the surface of the mineralized 2 kDa and 25 kDa PEI-collagen membranes, with more pronounced PI staining (Streptococcus mutans and Staphylococcus aureus) representing dead bacteria. Figure 8 Meanwhile, the amount of bacteria adhering to the PEI-collagen surface was significantly reduced. Furthermore, SEM observation showed that the bacteria ruptured, resulting in leakage of internal substances. Figure 8 (white dashed ellipse), while bacteria on the blank collagen membrane retain their original form ( Figure 8 ).
[0060] Previous studies have shown that polyethyleneimine, as a highly active antibacterial agent, can induce bacterial cell polarization and disrupt bacterial membrane structure. Our experimental results show that the cell membrane integrity of Staphylococcus aureus and Streptococcus mutans in the branched polyethyleneimine-collagen composite scaffold was disrupted, and the bacteria's adhesion to collagen fibers was significantly reduced, results consistent with previous literature reports. Considering its combined antibacterial properties, resistance to enzymatic hydrolysis, and high Young's modulus, the stability of the branched polyethyleneimine-collagen composite scaffold in clinical applications is significantly improved.
[0061] (6) Osteogenic activity of mineralized PEI-collagen Cellular response is another key parameter in the biological evaluation of PEI-collagen. To investigate the osteogenic induction capacity of mineralized PEI-collagen, cell adhesion, proliferation, and transcriptional levels of key genes and proteins were examined using rat bone marrow mesenchymal stem cells (BMSCs).
[0062] The CCK-8 results showed that cell growth was not inhibited in any of the three groups (Figure 7A). SEM morphology of BMSCs on different membrane materials revealed that BMSCs on mineralized PEI-collagen (2 kDa and 25 kDa) membranes were spindle-shaped or polygonal with numerous large, extended pseudopodia. In contrast, BMSCs seeded on blank collagen membranes were thin and elliptical, lacking obvious pseudopodia. Simultaneously, laser scanning confocal microscopy (LSCM) images showed that BMSCs on mineralized PEI-collagen membranes were spindle-shaped with elongated intracellular fibers and coarse actin profilosomes. BMSCs on blank collagen membranes, however, were elliptical and lacked pseudopodia. Both SEM and LSCM morphology indicate that BMSCs exhibited superior adhesion to PEI-collagen.
[0063] To assess the osteogenic induction capacity of mineralized PEI-collagen, the transcriptional levels of key osteogenic genes were detected by qRT-PCR. Results showed that after 14 days, the expression of alkaline phosphatase (ALP), type I collagen (COL1), osteopontin (OPN), runt-related transcription factor 2 (RUNX3), and vascular endothelial growth factor (VEGF) was significantly upregulated. The effect of mineralized PEI-collagen on osteogenic differentiation was further investigated by osteopontin (OPN) immunofluorescence staining. As shown in Figure 7, after 14 days of cell culture, a large number of cells in the mineralized PEI-collagen group showed positive staining for osteopontin (OPN), while the control group showed less OPN staining. The semi-quantitative analysis of immunofluorescence intensity was consistent with the OPN staining images (Figure 7Da).
[0064] Runt-associated transcription factor 2 (RUNX2), alkaline phosphatase (ALP), and type I collagen (COL1) are early markers of osteogenic development, while osteopontin (OPN) is expressed in late osteogenic differentiation. In BMSCs seeded on PEI-collagen membranes, the mRNA expression levels of both early and late osteogenic markers were enhanced, along with increased expression of vascular endothelial growth factor (VEGF). Numerous studies have reported on the response of BMSCs to microenvironment signals. In this study, collagen fibrils, which form the extracellular matrix (ECM), showed significantly increased surface stiffness after PEI grafting, and the mineralized collagen was rich in calcium phosphorus (CaP). Regarding the mechanism of increased osteogenic levels, according to Na et al., ECM stiffness may enhance osteogenic differentiation of BMSCs through regulation by Yes-associated protein (YAP). Extracellular uptake of calcium phosphorus (CaP) can also stimulate osteogenic differentiation of BMSCs through the Ras / Raf / ERK or phosphate-ATP-adenosine metabolic signaling pathways. PEI is a mature DNA delivery vector, and its antibacterial properties are usually associated with its inherent biotoxicity. To reduce its cytotoxicity, studies have often conjugated molecules such as cholesterol or bile acids to hydrophobic fragments of PEI. Molecular dynamics simulations show that PEI molecules bind to the hydrophobic interior of long collagen chains, indicating the possible existence of hydrophobic fragment connections, which could explain the positive results in osteogenic assays. The polyethyleneimine-collagen composite scaffold prepared according to this invention was observed using an electron microscope. Figure 8Image A is a high-resolution transmission electron microscopy (TEM) image showing that the c-axis of hydroxyapatite is parallel to the collagen fibers, consistent with the microstructure of natural bone. Image B is a TEM image showing periodically ordered mineralized collagen fibers, consistent with the microstructure of natural bone. Image C is a TEM image and selected area electron diffraction (SED) analysis showing that the inorganic phase in the mineralized collagen fibers is hydroxyapatite, consistent with the composition of natural bone. Image D is a scanning electron microscopy (SEM) image showing a mineralized collagen artificial bone repair material with pore sizes of 50–500 μm and a connected pore structure, consistent with the structure of natural cancellous bone.
[0065] Feasibility of extraction socket preservation surgery. Bilateral third mandibular premolars were extracted from four dogs, resulting in 16 alveolar sockets, which were randomly divided into three groups. Group A had 6 alveolar sockets, while groups B and C each had 5. Immediately after extraction, each alveolar socket in group A was filled with a polyethyleneimine-collagen composite scaffold and covered with a mineralized collagen-guided bone regeneration double-layer membrane. In group B, only a polyethyleneimine-collagen composite scaffold was implanted. Group C served as a blank control and no material was implanted. At 12 weeks post-surgery, the healing effect of the extraction sockets was assessed by gross observation, morphological measurements, and X-ray computed tomography. At 12 weeks post-surgery, new bone formation in groups A and B was significantly higher than in group C; alveolar bone height in group A was significantly lower than in groups B and C; bone mineral density and bone remodeling in the region of interest were higher in group A than in groups B and C. The results showed that mineralized collagen artificial bone extraction socket filling can guide the regeneration of new bone in the extraction socket, and the mineralized collagen artificial bone extraction socket filling and mineralized collagen guided bone regeneration double membrane can further reduce alveolar ridge resorption and preserve the extraction socket site.
[0066] In summary, after reading this invention document, those skilled in the art can make various other corresponding modifications to the technical solutions and concepts based on this invention without creative mental effort, and all of these modifications fall within the scope of protection of this invention.
Claims
1. A method for preparing a polyethyleneimine-collagen composite scaffold, characterized in that, Includes the following steps: S1: Construction of PEI-collagen scaffold; S2: Mineralization of PEI-collagen.
2. The method for preparing a polyethyleneimine-collagen composite scaffold according to claim 1, characterized in that, Step S1 includes the following steps: The collagen material is immersed in the polyethyleneimine solution to carry out a cross-linking reaction, thereby obtaining a polyethyleneimine-collagen composite scaffold precursor.
3. The method for preparing a polyethyleneimine-collagen composite scaffold according to claim 2, characterized in that, The concentration of the polyethyleneimine solution is from 0.5 mM to 5 mM; the polyethyleneimine solution contains a crosslinking agent, which includes 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide.
4. The method for preparing a polyethyleneimine-collagen composite scaffold according to claim 2, characterized in that, The crosslinking reaction is carried out in a buffer solution with a pH of 5.0-6.0, at a temperature of 15-30°C, and for a time of 12-48 hours.
5. The method for preparing a polyethyleneimine-collagen composite scaffold according to claim 1, characterized in that, Step S1 includes the following steps: PEI was dissolved in 0.1 M morpholine ethanesulfonic acid containing 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide for esterification, and then incubated with a collagen membrane at room temperature.
6. The method for preparing a polyethyleneimine-collagen composite scaffold according to claim 5, characterized in that, Step S1 also includes the following steps: The membrane sample was rinsed with distilled water to obtain the PEI-collagen model.
7. The method for preparing a polyethyleneimine-collagen composite scaffold according to claim 1, characterized in that, Step S2 includes the following steps: The composite scaffold is immersed in a mineralization solution containing calcium and phosphate ions and mineralized at 30-40°C for 5-20 days to obtain a mineralized polyethyleneimine-collagen composite scaffold.
8. A polyethyleneimine-collagen composite scaffold, characterized in that, The scaffold was prepared using the method described in any one of claims 1-7 for preparing a polyethyleneimine-collagen composite scaffold.
9. An application of a polyethyleneimine-collagen composite scaffold, characterized in that, Application of the polyethyleneimine-collagen composite scaffold prepared by the method described in any one of claims 1-7 in bone defect repair, bone tissue regeneration, or bone infection control.
10. The application of the polyethyleneimine-collagen composite scaffold according to claim 9, characterized in that, The polyethyleneimine-collagen composite scaffold is used as a bone filler, bone tissue engineering scaffold, or coating.